THE TRANSFORMATIVE ROLE OF INFORMATION TECHNOLOGY IN EDUCATION (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In the contemporary era, the integration of Information Technology (IT) in education has revolutionized traditional learning paradigms, fostering a dynamic and interconnected educational landscape. This abstract delves into the multifaceted impact of IT on education, exploring its role in fostering accessibility, personalized learning experiences, and global collaboration. We examine how IT optimizes resources for educators, promotes lifelong learning opportunities, and contributes to the globalization of education. While acknowledging the transformative potential, we also highlight the challenges associated with the digital divide, data privacy concerns, and the imperative of digital literacy. This abstract encapsulates the essence of the article, emphasizing the need for collaborative efforts to ensure equitable and responsible integration of information technology in education